ORAL MUCOSAL CANDIDIASIS IN CHILDREN: CLINICAL COURSE, DIAGNOSIS AND TREATMENT (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Oral mucosal candidiasis is one of the most common fungal infections in pediatric practice. The disease is predominantly caused by Candida albicans, although other Candida species are increasingly recognized as important pathogens. Oral candidiasis affects newborns, infants, and immunocompromised children more frequently, leading to discomfort, feeding difficulties, and reduced quality of life. The clinical manifestations vary from pseudomembranous and erythematous forms to chronic hyperplastic lesions. Early diagnosis and appropriate treatment are essential to prevent complications and recurrence. This review analyzes current data on the epidemiology, clinical course, diagnostic approaches, and treatment strategies for oral candidiasis in children. Particular attention is paid to risk factors, laboratory diagnostic methods, and modern antifungal therapies. The findings emphasize the importance of comprehensive management, including antifungal treatment, correction of predisposing factors, and maintenance of oral hygiene.
Keywords: Oral candidiasis, pediatric dentistry, Candida albicans, oral mucosa, fungal infection, diagnosis, antifungal therapy, children.